Modeling of grayscale lithography and calibration with experimental data for blazed gratings - Bhardwaj, Pankaj; Erdmann, Andreas; Leitel, Robert (Proceedings of SPIE - The International Society for Optical Engineering, 2021)
This paper discusses a collaborative effort of two Fraunhofer institutes to develop a lithography model that simulates the fabrication of blazed gratings using grayscale lithography. The model is calibrated with experimental data of blazed grating profiles. The complete process of modeling and calibration has been performed using the research and development lithography simulator Dr.LiTHO. To emulate the grayscale exposure of blazed gratings in a LED-based micro-image stepper with Dr.LiTHO a thin mask with a linear variation of the mask transmission and corresponding distribution of exposure dose was used. The resulting photoresist profiles are obtained with a standard model for Diazonaphthoquinone (DNQ) photoresists. The calibration of simulated and experimental profile data of blazed gratings is performed using Dr.LiTHO's inbuilt optimizer - Pythmea. The difference between experimental and simulated profile shapes is expressed by an areaFit. Minimization of this areaFit versus photoresist parameters and correlation analysis help to identify the most appropriate model parameters.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Blazed gratings; Calibration; Grayscale lithography; Graytone lithography; Modeling; Sensitivity analysis